An Analysis of Students’ Difficulties in Writing Descriptive Paragraph - Jusnaini Hasni Jusnaini Hasni (Faculty of Letters Universitas Balikpapan, 2023)
This study analyzed the students' difficulties in writing descriptive text through vocabulary, grammatical error, and unorganized writing problems. This study conducted a case study as qualitative research on students in 3rd grade at SMPN 1 Kuta Panjang Gayo Lues. The sample consisted of 10 students by using purposive sampling. This study used observation and interview methods. The students write a descriptive text according to the topic given by the researcher. Then, the researcher categorized and analyzed the students’ work. The result of the study showed that the students’ ability to write descriptive paragraphs is still low, and they face some difficulties in learning English.